Assessment of Cultural and Contextual Factors in Trauma-Informed Interventions for Internally Displaced People in Ethiopia: A Community-Based Participatory Action Research - Waganesh A. Zeleke; Mengistu Dagnew; Yemataw Wondie; Tewodros Hailu; Courtney Holmes; Mekdes Melesse Mekonen; Birtukan Taye Eshete; Goshu Nenko (Trauma Care)
Background: Internal displacement is a global crisis, with Ethiopia being among the most affected countries due to conflict, violence, and natural disasters. Internally displaced people (IDPs) face multifaceted trauma at the individual, family, and community levels, exacerbating mental health issues such as PTSD and depression. Despite ongoing interventions, many programs lack cultural and contextual adaptations that are suited to Ethiopia’s diverse communities. Aims: This study aimed to explore the cultural and contextual factors influencing trauma-informed interventions for IDPs in Ethiopia and develop a framework for culturally responsive mental health support. Methods: Utilizing Community-Based Participatory Action Research (CBPAR) and interpretative phenomenological research design, data were collected from 42 stakeholders through Focus Group Discussions and in-depth individual interviews, and subsequently analyzed using thematic analysis to identify patterns and themes. Results: Key findings highlighted the ongoing trauma faced by IDPs, the importance of demographic characteristics (e.g., gender and education), and the role of cultural stereotypes in shaping trauma perceptions. Traditional community rituals such as coffee ceremonies have been identified as vital for healing. Effective interventions require cultural alignment, respect for religious values, and integration into community activities. Conclusions: This study underscores the need for culturally and contextually responsive trauma-informed intervention. Incorporating community rituals and engaging local leaders enhances intervention acceptance and effectiveness. The findings provide a framework to address mental health needs while fostering resilience among internally displaced Ethiopian populations.